Degradation of Kuntau Martial Art In The Village of Dawas Musi Regency Banyuasin - Siti Hesti Puspa Vera; Apriana Apriana; Yuliarni Yuliarni (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2023)
Kuntau is one of the martial arts that is known by the people of South Sumatra, but as time went on, kuntau began to be pushed aside and replaced by modern martial arts. This study aims to determine the history of the formation of the Kuntau martial art in Dawas Village, Musi Banyuasin Regency, its growth and development and to determine the factors causing the degradation of the Kuntau martial art in Dawas Village, Musi Banyuasin Regency. In this study using historical methods and data collection techniques carried out through observation, interviews and documentation. After the data is collected, it is continued with data analysis and drawing conclusions. The history of the formation of the Kuntau martial art in Dawas Village in 1943 was brought by an ancestor named Puyang Pasirah. In the 1950s the Kuntau art began to experience rapid development and had a lot of interest for the community in this field, because this martial art was very much needed at that time. But over time, the Kuntau martial art began to experience degradation around the 1980s